How to be a leader - Bjergegaard, Martin, ....- (London : Macmillan, 2016)
No one is born to lead. This is the idea at the heart of this thoughtful book on leadership. Popular culture feeds us images of the square-jawed, strong-armed leader - charismatic, powerful, decisive - but the truth is, with the right amount of self-knowledge and authenticity, anyone can be a good leader, even those who don't fit the stereotype. There are countless courses and books available on leadership technique, decision-making and public speaking, but How to Be a Leader aims to give you the tools to understand and bring out your own leadership style. With an in-depth look at what it really means to lead, and the difference between being a manager and being a leader, How to Be a Leader invites you to explore - and accept - the unique leader in you.
Keywords: Leiderschap